MEMORY, BIAFRA AND THE QUESTION OF NATIONHOOD IN BIYI BANDELE’S HALF OF A YELLOW SUN - Adebisi, Ademakinwa, Dr. (International Review of Humanities Studies, 2020)
The essential place of film in engaging the idea of memory and collective memory is established by the fact of its historical origins and development over the centuries. This, in every sense is connected to the socio-cultural, political as well as economic and aesthetic evolution, influenced and controlled by the reality of the people’s experience. From classical to the contemporary times, film makers have drawn montage-like pictures of their world, in concrete terms as historical films for the world to see. However, through the approaches of Social Interaction and Trauma Theories, Image Analysis and Historical Contextualization, this paper interrogates Biyi Bandele’s Half of a Yellow Sun, an adaptation of Chimamanda Adichie’s novel of the same title and how it has been deployed as a tool for the construction of collective memory of the Biafra/ Nigerian civil war experience. Data were collated through library research and critical study of related films. The findings therefore, reveal that memory plays cogent roles in the process of reconstruction of history. The film therefore serves as a point of reference for Nigerians to have reminiscence over the negative effects of the war on the people. It is however clear that the agitation by some groups to call for the renegotiation of the country’s unity is meant for the purpose of self- interest rather than collective. The reconstruction of the memory of agony of the war in the film, if not properly managed could be burdensome to the country, and may degenerate into another internal crisis. Hence, there is the need for any aggrieved party to be cautious in their approaches towards the question of National unity and perceived marginalization.